Socio-economic benefits of using green materials for the construction of low-cost buildings in Nigeria - Adeniyi, Shogo Musbau (Global Society of Scientific Research and Researchers, 2020)
It is explicit that earth and other green materials as been in use from time immemorial for construction of building at an affordable price before civilisation and adoption of conventional materials for construction works. However, in the resent era, the price of housing as increased to the extent that it is beyond the capacity of lower and middle class to construct or buy building of their own. Therefore, this paper is assessing the socio-economic benefits of using green materials for erection of structure at affordable prices. A quantitative method was adopted in carrying out this study using purposive sampling approach in data collection. Four hundred structured survey instruments circulated among the construction professionals in the north-central part of Nigeria, seeking their views on the benefits of using green materials towards provision of building at reasonable price. The responses received (76.20%), were analysed using analysis of moments (AMOS) via structural equation model (SEM). The results show that green material is cost-effective, readily available, energy efficiency, reduced cost of construction, reduced waste, improved the economy of the community promotes cultural heritage, adaptable to the environment, eco-friendly, enhance social wellbeing, and reduced carbon dioxide emission. Therefore, it is recommended that an integration of green materials will promote provision of more buildings to the citizenry at affordable rate.